Environment-friendly copper deposition agent and preparation method and application thereof

By using the synergistic effect of quaternized chitosan complexing agent, chitosan-cysteine ​​derivative and chitosan-glutathione derivative in the copper depositing agent, the balance between environmental protection and deposition performance of existing copper depositing agents is solved, and efficient and stable copper layer deposition and environmental protection performance are achieved.

CN119876923AActive Publication Date: 2025-04-25XINFENG ZHENGTIANWEI ELECTRONICS TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510361370.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The existing copper depositing agent has not yet reached a good balance between environmental protection and deposition properties. The traditional complexing agent has poor biodegradability, resulting in environmental pollution and unstable quality of the deposited layer.

Method used

The synergistic effect of quaternized chitosan complexing agent, chitosan-cysteine ​​derivative and chitosan-glutathione derivative is adopted to form a spatial topological structure with multi-layer complexing ability through the acetic acid-ethanol mixed solvent system and suitable preparation conditions, thereby achieving efficient complexing and deposition control of copper ions.

Benefits of technology

The complexing stability, redox regulation ability and deposition uniformity of the copper depositing agent are improved, the high quality and reliability of the copper layer are ensured, the high standard needs in the electronic manufacturing field are met, and the risk of environmental pollution is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876923A_ABST
    Figure CN119876923A_ABST
Patent Text Reader

Abstract

The invention relates to the field of copper deposition materials, and provides an environment-friendly copper deposition agent and a preparation method thereof. The copper deposition agent comprises a quaternized chitosan complexing agent, a chitosan-cysteine derivative, a chitosan-glutathione derivative, tea polyphenol, dopamine, potassium trihydrate, citric acid, ascorbic acid, glucose, sodium alginate, sodium citrate and an ethanol-water mixed solvent. The preparation method comprises the steps of synthesis of the chitosan derivative, preparation of the complexing agent and preparation of the copper deposition agent, and the adhesion and uniformity of a deposition layer are improved by optimizing the stability of the complexing agent, the copper ion complexing ability and the deposition uniformity. The obtained copper deposition agent solution is stable in conductivity, controllable in copper deposition rate and suitable for electronic circuit manufacturing and metal surface treatment. A natural polymer complexing agent is adopted to replace a traditional harmful complexing agent, efficient and environment-friendly copper deposition is achieved, environmental pollution is reduced, and good industrial application value is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of copper deposition materials, and in particular to an environmentally friendly copper deposition agent and a preparation method and application thereof. Background Art

[0002] In industries such as electronic circuit manufacturing, printed circuit board (PCB) processing, and metal surface treatment, copper plating processes are widely used to form conductive layers to ensure circuit reliability and conductivity. As electronic products evolve towards higher density, lighter weight, and higher performance, the uniformity, adhesion, and conductivity of the copper plating layer have become key performance indicators. Furthermore, the environmental friendliness of the process is also gaining increasing attention. In practical applications, copper plating agents must possess excellent complexing properties to stabilize copper ions and control the deposition rate, ensuring a uniform and defect-free coating. Furthermore, to accommodate the processing requirements of diverse substrates and complex structures, copper plating agents must also exhibit good stability to prevent abnormal precipitation and deposited layer defects during the deposition process. With increasingly stringent environmental regulations, copper plating agents containing EDTA, ammonia complexes, or formaldehyde systems, commonly used in traditional copper plating processes, are facing restrictions due to environmental pollution concerns. Therefore, developing an environmentally friendly copper plating agent that balances deposition performance and environmental friendliness would not only help improve the greenness of electronics manufacturing processes but also promote sustainable development in the field, meeting the industry's urgent need for high-performance, low-pollution copper plating processes.

[0003] However, common copper precipitating agent in the market relies on traditional chelating agent mostly, such as EDTA and derivatives thereof, although these chemical substances can provide good copper ion complexing ability, but its biodegradability is poor, easily causes heavy metal pollution in waste liquid treatment process, increases environmental management cost.As the Chinese patent that publication number is CN101698936B discloses sodium hypophosphite disodium ethylenediaminetetraacetic acid system chemical copper plating solution, although can improve deposition rate and improve coating quality, the chelating agent it uses has higher environmental risk, needs to strictly control waste liquid discharge.In addition, part copper precipitating process adopts formaldehyde as reducing agent, but formaldehyde has stronger toxicity and volatility, and there is health and safety hidden danger in long-term service. Meanwhile, though part environmentally friendly copper precipitating agent adopts chelating agents such as citric acid or amino acid to replace EDTA, because its complexing ability is relatively weak, causes copper ion complexing instability, easily occurs the problems such as deposition rate uneven, coating adhesion deficiency in sedimentation process. Therefore, the existing technology has not yet achieved a good balance between environmental protection and deposition performance, and the selection and formulation design of complexing agents still need to be further optimized to ensure the quality and stability of the deposited layer while improving the environmental protection of the copper plating process. Summary of the Invention

[0004] (1) Technical problems solved The purpose of the present invention is to provide an environmentally friendly copper deposition agent and a preparation method and application thereof, so as to solve the problems of the current copper deposition agent in terms of environmental protection and insufficient deposition performance.

[0005] (2) Technical solution In order to achieve the above object, the present invention provides the following technical solutions: An environmentally friendly copper plating agent comprises the following raw materials in parts by weight: 8-15 parts of a quaternized chitosan complexing agent, 5-10 parts of a chitosan-cysteine ​​derivative, 2.5-6.0 parts of a chitosan-glutathione derivative, 2.0-6.0 parts of tea polyphenols, 2.5-6.0 parts of dopamine, 10-20 parts of potassium citrate trihydrate, 2-6 parts of ascorbic acid, 2-5 parts of glucose, 0.5-2 parts of sodium alginate, 0.5-2.0 parts of sodium citrate, and 50-80 parts of an ethanol-water mixed solvent.

[0006] Furthermore, the quaternized chitosan complexing agent is prepared by swelling chitosan with a deacetylation degree of 80-95% and a molecular weight of 100-300 kDa in an acetic acid-ethanol mixed solvent, reacting the chitosan with 2,3-epoxypropyltrimethylammonium chloride under heating and reflux conditions, and then precipitating, washing, and vacuum drying. The chitosan-cysteine ​​derivative is prepared by swelling chitosan with a deacetylation degree of 80-95% and a molecular weight of 50-200 kDa in an acidic aqueous solution, reacting the mixture with pre-activated L-cysteine ​​under stirring conditions, and freeze-drying the mixture. The chitosan-glutathione derivative is prepared by swelling chitosan with a deacetylation degree of 80-95% and a molecular weight of 50-200 kDa in an acidic aqueous solution, stirring and reacting the chitosan with glutathione and a cross-linking agent under suitable pH conditions, and freeze-drying the mixture.

[0007] Furthermore, the preparation method of the quaternized chitosan complexing agent is as follows: in parts by weight, 30 to 60 parts of a 1 wt.% acetic acid aqueous solution and 30 to 60 parts of ethanol are mixed to form a solvent system, 1.5 to 2.0 parts of chitosan are added, stirred and swelled for 120 to 180 minutes, and then 3.5 to 4.5 parts of 2,3-epoxypropyltrimethylammonium chloride are added, and reflux reaction is carried out at 75 to 85° C. for 10 to 14 hours. After the reaction is completed, the system is cooled to 25 to 30° C., 500 to 800 parts of acetone are added to precipitate the product, and the precipitate is collected and then centrifuged and washed 3 to 5 times with a mixed solvent of anhydrous ether and acetone, wherein the volume ratio of anhydrous ether to acetone is 1:(10 to 13), and finally vacuum dried at -0.08 to 0.10 MPa and 40 to 60° C. for 12 to 24 hours to obtain the quaternized chitosan complexing agent.

[0008] The present invention adopts the design of quaternized chitosan complexing agent mainly for enhancing the complexing stability and deposition uniformity of copper precipitation agent. The chitosan is fully swollen by the acetic acid-ethanol mixed solvent system, ensuring the three-dimensional extension of the molecular chain, and providing uniformly exposed active sites for the subsequent quaternization reaction. Under precisely controlled heating and reflux conditions, the epoxy group of 2,3-epoxypropyltrimethylammonium chloride and the chitosan amino group undergo an efficient ring-opening reaction to form a stable quaternized structure, and the reaction activity is optimized by regulating the polarity of the solvent to achieve hydrophilicity regulation and uniform charge distribution of the chitosan skeleton, so that it exhibits significant electrostatic adsorption capacity and complexing stability in solution. Acetone precipitation is used to preliminarily remove unreacted products, and combined with anhydrous ether-acetone composite washing to further improve the purity of the product. At the same time, the vacuum drying conditions are precisely controlled to avoid structural collapse caused by severe desolvation, ensuring the uniform distribution and complexing activity of the quaternary ammonium group. The synergistic effects of the various components are manifested in the following ways: the acetic acid-ethanol system promotes the swelling of chitosan through the hydrogen bonding effect of acetic acid, while ethanol regulates the solvent polarity to optimize the molecular structure; the steric effect and charge characteristics of epoxypropyltrimethylammonium chloride synergistically enhance the copper ion complexing ability; gradient washing with polar solvents improves the chemical purity, while mild drying conditions ensure the complexing stability and deposition control ability of the product, ultimately forming a spatial topological structure with multi-level complexing ability, realizing precise control of the copper ion migration rate and deposition behavior.

[0009] Furthermore, the preparation method of the chitosan-cysteine ​​derivative is as follows: 1.0 to 5.0 parts of chitosan are dispersed in 50 to 150 parts of a 1.0 to 1.5 wt.% hydrochloric acid aqueous solution by weight, and the mixture is stirred and swelled for 30 to 60 minutes to form a homogeneous solution; 0.5 to 3.0 parts of L-cysteine ​​are dissolved in 50 to 100 parts of deionized water, 0.1 to 0.5 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added, and the activation time is controlled to be 15 to 30 minutes; the activated cysteine ​​solution is slowly added dropwise to the chitosan solution, the pH of the system is adjusted to 4.0 to 5.5 with a 1 vol.% hydrochloric acid solution, and the reaction is continuously stirred at 25 to 40° C. for 4 to 8 hours. After the reaction is completed, the solution is freeze-dried for 24 to 48 hours to obtain the chitosan-cysteine ​​derivative.

[0010] The present invention adopts the design of chitosan-cysteine ​​derivatives mainly for enhancing the complexing ability and coating adhesion performance of copper precipitating agent. Chitosan molecules are controllably swollen by hydrochloric acid aqueous solution system, so that its molecular chain is fully extended and amino active sites are activated by protonation, providing a structural basis for subsequent chemical modification. 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride generates a highly reactive intermediate by selectively activating the carboxyl group of L-cysteine, and forms an amide bond with chitosan amino group under weakly acidic conditions, thereby realizing the precise grafting of sulfhydryl functional groups. The synergistic optimization of swelling degree, activation efficiency and reaction pH ensures the uniform distribution and spatial orientation of sulfhydryl groups on the chitosan skeleton, forming a multi-level coordination network, and synergistically improving the complexing stability by the strong coordination effect of sulfhydryl-copper ions and the chelating effect of chitosan skeleton, while enhancing the bonding strength of the coating to the substrate by interfacial chemical bonding.

[0011] Furthermore, the preparation method of the chitosan-glutathione derivative is as follows: in parts by weight, 0.2 to 0.5 parts of chitosan-glutathione derivative are dispersed in 1.8 to 3.0 parts of 1.0 to 1.2 mol / L hydrochloric acid aqueous solution, 8 to 15 parts of deionized water are added to form a colloidal dispersion system with a polymer concentration of 0.8% to 1.5 wt.%, the pH of the system is adjusted to 5.5 to 6.5 with 1 vol.% hydrochloric acid, and then 1.5 to 3.0 parts of a 200 to 300 mg / mL solution is added. Glutathione aqueous solution; adding 0.1-0.3 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.05-0.15 parts of N-hydroxysuccinimide in sequence, maintaining the pH value at 5.8-6.2, and reacting with magnetic stirring at 15-30°C for 12-24 hours; freeze-drying the solution after the reaction at -70-90°C and 0.01-0.05MPa for 36-72 hours to obtain a chitosan-glutathione derivative.

[0012] The present invention adopts the design of chitosan-glutathione derivatives, which is mainly used to enhance the antioxidant stability and complexing ability of copper depositing agents. Through chemical modification of chitosan and glutathione, sulfhydryl and carboxyl functional groups are introduced, which can effectively complex copper ions during the copper deposition process, while providing antioxidant protection and reducing the risk of premature reduction of copper ions, thereby improving the uniformity and stability of the deposited layer. Chitosan is dispersed in a hydrochloric acid aqueous solution of appropriate concentration to form a colloidal system, ensuring the full expansion of its molecular chain and improving the subsequent binding efficiency with glutathione. Under appropriate pH regulation, the addition of glutathione solution further gives chitosan stronger complexing and antioxidant ability, while the synergistic effect of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N-hydroxysuccinimide promotes the stable chemical bonding between chitosan and glutathione, improving the structural stability and chemical activity of the derivative. The long-term reaction under suitable temperature and stirring conditions ensures the full combination of functional groups. At the same time, the low-temperature freeze-drying process avoids the damage to the structure of chitosan and glutathione caused by high temperature, thereby maintaining their excellent solubility and functional activity.

[0013] Furthermore, the volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:(2.0-4.5); Furthermore, the solution conductivity of the copper plating agent is controlled at 5-15 mS / cm; Furthermore, the copper deposition rate of the copper deposition agent is 1.5-3.0 μm / min; The present invention also provides a method for preparing an environmentally friendly copper plating agent, comprising the following steps: S1. Dissolve the quaternized chitosan complexing agent, chitosan-cysteine ​​derivative, and chitosan-glutathione derivative in an ethanol-water mixed solvent according to the ratio. The dissolution process is carried out at a stirring rate of 400-600 rpm for 30-60 min and the system temperature is controlled at 25-35°C. S2. Preparation of prepolymer solution: Add tea polyphenols, dopamine, potassium citrate trihydrate, ascorbic acid and glucose to the dissolved system in sequence, maintain the temperature at 25-35°C, and mix at a stirring speed of 300-500 rpm until completely dissolved. The total addition time is controlled within 10-20 min.

[0014] S3. Prepare the coating: Slowly add sodium alginate and sodium citrate to adjust the pH of the system to 4.5-6.5. Continue stirring at 400-600 rpm for 30-60 min to ensure the system is uniform and stable. After the final solution is filtered through a 0.45 μm filter membrane, stand in the dark at 4-8°C for 12-24 h to complete the aging process.

[0015] The present invention also discloses the application of an environmentally friendly copper deposition agent in the manufacture of electronic circuits, printed circuit copper deposition, electromagnetic shielding coatings and flexible electronic devices.

[0016] The present invention adopts an environmentally friendly copper deposition agent designed to enhance the complexing stability, redox control ability and deposition uniformity of the deposition system. Through the synergistic effect of quaternized chitosan complexing agent, chitosan-cysteine ​​derivatives and chitosan-glutathione derivatives, efficient complexing and deposition control of copper ions are achieved. Among them, the quaternized chitosan complexing agent improves solubility and complexing stability, the chitosan-cysteine ​​derivative enhances the adhesion of the coating, and the chitosan-glutathione derivative prevents premature reduction of copper ions, ensuring uniform deposition. In the ethanol-water mixed solvent system, the temperature and stirring rate are controlled to ensure that the complexing agent is fully dissolved and evenly dispersed. Tea polyphenols and dopamine further enhance antioxidant capacity and regulate the release rate of copper ions through complexation. Potassium citric acid trihydrate and ascorbic acid construct a stable pH buffer system and dynamically regulate the deposition behavior of copper. Glucose optimizes the deposition environment and improves system stability. Sodium alginate and sodium citrate ensure the uniformity and rheological properties of the coating and optimize the complexing state of copper ions. The system is filtered through a membrane and aged at low temperature to ensure the long-term stability and deposition activity of the copper precipitate. This invention, through complexing agent optimization and multi-component synergy, enhances the complexing stability, redox controllability, and deposition uniformity of the copper precipitate, ensuring its efficient application in electronic circuit manufacturing, printed circuit copper deposition, electromagnetic shielding coatings, and flexible electronic device manufacturing.

[0017] (3) Beneficial technical effects 1. The present invention improves the stability and uniformity of the copper deposition agent by using a quaternized chitosan complexing agent. The various components synergistically optimize the complexing ability, purity, and deposition control, achieving precise migration of copper ions, improving process consistency, reducing defects, and meeting the high standards of electronic manufacturing.

[0018] 2. This invention enhances the copper plating agent's complexing ability and coating adhesion through precise modification of chitosan-cysteine ​​derivatives. Swelling control, activation optimization, and pH adjustment synergistically ensure uniform distribution of thiol groups, construct a multi-level coordination network, enhance copper ion complexing stability and coating adhesion, and improve deposition uniformity and reliability.

[0019] 3. This invention enhances the antioxidant stability and complexing capacity of copper deposits through precise modification of chitosan-glutathione derivatives. The thiol and carboxyl groups synergistically complex copper ions, preventing premature reduction and improving the uniformity of the deposited layer. pH control, chemical bonding, and freeze-drying optimize the derivative's stability, ensuring efficient application.

[0020] 4. This invention utilizes quaternized chitosan to improve solubility and complex stability, chitosan-cysteine ​​derivatives to enhance coating adhesion, and chitosan-glutathione derivatives to prevent premature reduction of copper ions. Tea polyphenols and dopamine enhance antioxidant capacity, potassium trihydrate, citric acid, and ascorbic acid create a pH buffer system to regulate deposition, glucose optimizes the deposition environment, and sodium alginate and sodium citrate ensure coating uniformity, enhancing the stability of the copper deposition system and making it suitable for use in electronics manufacturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the infrared Fourier spectrum of the chitosan-cysteine ​​derivative prepared in Example 1 of the present invention.

[0022] Figure 2 This is the morphology of through-hole copper plating prepared based on the copper deposition agent prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] To make the objectives, technical solutions and advantages of the embodiments of the present invention more clear, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.

[0024] Example 1 An environmentally friendly copper plating agent comprises the following raw materials in parts by weight: 8 parts of a quaternized chitosan complexing agent, 5 parts of a chitosan-cysteine ​​derivative, 2.5 parts of a chitosan-glutathione derivative, 2.0 parts of tea polyphenols, 2.5 parts of dopamine, 10 parts of potassium citric acid trihydrate, 2 parts of ascorbic acid, 2 parts of glucose, 0.5 part of sodium alginate, 0.5 part of sodium citrate, and 50 parts of an ethanol-water mixed solvent.

[0025] The quaternized chitosan complexing agent was prepared by swelling chitosan with a deacetylation degree of 80% and a molecular weight of 100 kDa in an acetic acid-ethanol mixed solvent, reacting it with 2,3-epoxypropyltrimethylammonium chloride under heating reflux conditions, and then precipitating, washing, and vacuum drying. The chitosan-cysteine ​​derivative was prepared by swelling chitosan with a deacetylation degree of 80% and a molecular weight of 50 kDa in an acidic aqueous solution, reacting it with preactivated L-cysteine ​​under stirring conditions, and then freeze-drying. The polysaccharide-glutathione derivative was prepared by swelling chitosan with a deacetylation degree of 80% and a molecular weight of 50 kDa in an acidic aqueous solution, reacting it with glutathione and a cross-linking agent under stirring conditions at an appropriate pH, and then freeze-drying.

[0026] The preparation method of the quaternized chitosan complexing agent comprises the following steps: in parts by weight, 30 parts of a 1 wt.% acetic acid aqueous solution and 30 parts of ethanol are mixed to form a solvent system, 1.5 parts of chitosan are added, stirred and swelled for 120 minutes, and then 3.5 parts of 2,3-epoxypropyltrimethylammonium chloride are added. The reaction is refluxed at 75°C for 10 hours. After the reaction is completed, the system is cooled to 25°C, 500 parts of acetone are added to precipitate the product, the precipitate is collected and then centrifuged and washed three times with a mixed solvent of anhydrous ether and acetone, wherein the volume ratio of anhydrous ether to acetone is 1:10, and finally vacuum dried at -0.08 MPa and 40°C for 12 hours to obtain the quaternized chitosan complexing agent.

[0027] The preparation method of the chitosan-cysteine ​​derivative is as follows: 1.0 part of chitosan is dispersed in 50 parts of a 1.0 wt.% hydrochloric acid aqueous solution, and the mixture is stirred and swelled for 30 minutes to form a homogeneous solution; 0.5 parts of L-cysteine ​​are dissolved in 50 parts of deionized water, 0.1 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added, and the activation time is controlled to be 15 minutes; the activated cysteine ​​solution is slowly added dropwise to the chitosan solution, the pH of the system is adjusted to 4.0 with a 1 vol.% hydrochloric acid solution, and the reaction is continuously stirred at 25°C for 4 hours. After the reaction is completed, the solution is freeze-dried for 24 hours to obtain the chitosan-cysteine ​​derivative.

[0028] The preparation method of the chitosan-glutathione derivative is as follows: 0.2 parts by weight are dispersed in 1.8 parts of a 1.0 mol / L hydrochloric acid aqueous solution, 8 parts of deionized water are added to form a colloidal dispersion system with a polymer concentration of 0.8 wt.%, the pH of the system is adjusted to 5.5 with 1 vol.% hydrochloric acid, and then 1.5 parts of a 200 mg / mL glutathione aqueous solution are added; 0.1 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.05 parts of N-hydroxysuccinimide are added in sequence, the pH value is maintained at 5.8, and the reaction is carried out under magnetic stirring at 15°C for 12 hours; the reaction solution is freeze-dried at -70°C and 0.01 MPa for 36 hours to obtain the chitosan-glutathione derivative.

[0029] The volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:2.0; the solution conductivity of the copper deposition agent is controlled at 5 mS / cm; and the copper deposition rate of the copper deposition agent is 1.5 μm / min.

[0030] The preparation method of an environmentally friendly copper plating agent of this embodiment includes the following steps: S1. Dissolve the quaternized chitosan complexing agent, chitosan-cysteine ​​derivative, and chitosan-glutathione derivative in an ethanol-water mixed solvent according to the ratio. The dissolution process is carried out at a stirring rate of 400 rpm for 30 min and the system temperature is controlled at 25°C. S2. Preparation of prepolymer solution: tea polyphenols, dopamine, potassium citrate trihydrate, ascorbic acid and glucose were added to the dissolved system in sequence, the temperature was maintained at 25°C, and the stirring speed was 300 rpm until completely dissolved. The total addition time was controlled within 10 min. S3. Prepare the coating: Slowly add sodium alginate and sodium citrate, adjust the pH of the system to 4.5, and continue stirring at 400 rpm for 30 min to ensure the system is uniform and stable. After the final solution is filtered through a 0.45 μm filter membrane, stand it in the dark at 4°C for 12 h to complete the aging process.

[0031] Depend on Figure 1 The chitosan-cysteine ​​derivative (Cys-CS) prepared in this invention exhibits additional infrared spectra, compared to chitosan, for the amide group absorption peak at 1637 cm⁻¹ and the SH stretching vibration peak at 2550 cm⁻¹, indicating successful grafting of cysteine ​​onto the chitosan molecular chain, forming a stable chemical bond. This structure imparts enhanced complexing capacity and chemical stability to the material, facilitating efficient copper ion binding and controlled release. Figure 2 The excellent performance of the copper precipitant of the present invention in through-hole copper electroplating was further verified. The deposited copper layer was uniform and had strong bonding force, which proved that the optimized design of the complexing agent effectively improved the deposition quality and reliability, thereby ensuring the application value of the copper precipitant in the fields of electronic circuit manufacturing and so on.

[0032] Example 2 An environmentally friendly copper plating agent comprises the following raw materials in parts by weight: 10 parts of a quaternized chitosan complexing agent, 7 parts of a chitosan-cysteine ​​derivative, 3.5 parts of a chitosan-glutathione derivative, 3.2 parts of tea polyphenols, 3.5 parts of dopamine, 13 parts of potassium citric acid trihydrate, 3 parts of ascorbic acid, 3 parts of glucose, 1.0 part of sodium alginate, 1.0 part of sodium citrate, and 59 parts of an ethanol-water mixed solvent.

[0033] The quaternized chitosan complexing agent was prepared by swelling chitosan with a deacetylation degree of 84% and a molecular weight of 160 kDa in an acetic acid-ethanol mixed solvent, reacting it with 2,3-epoxypropyltrimethylammonium chloride under heating and reflux conditions, followed by precipitation, washing, and vacuum drying. The chitosan-cysteine ​​derivative was prepared by swelling chitosan with a deacetylation degree of 84% and a molecular weight of 95 kDa in an acidic aqueous solution, reacting it with preactivated L-cysteine ​​under stirring conditions, and freeze-drying. The polysaccharide-glutathione derivative was prepared by swelling chitosan with a deacetylation degree of 84% and a molecular weight of 95 kDa in an acidic aqueous solution, reacting it with glutathione and a cross-linking agent under stirring conditions at an appropriate pH, and then freeze-drying.

[0034] The preparation method of the quaternized chitosan complexing agent is as follows: 39 parts of 1wt.% acetic acid aqueous solution and 39 parts of ethanol are mixed to form a solvent system, 1.7 parts of chitosan are added, and the mixture is stirred and swelled for 138 minutes, followed by adding 3.8 parts of 2,3-epoxypropyltrimethylammonium chloride, and refluxed at 78°C for 11 hours. After the reaction is completed, the system is cooled to 26°C, 590 parts of acetone are added to precipitate the product, the precipitate is collected and then centrifuged and washed four times with a mixed solvent of anhydrous ether and acetone, wherein the volume ratio of anhydrous ether to acetone is 1:11, and finally vacuum dried at -0.09 MPa and 46°C for 16 hours to obtain the quaternized chitosan complexing agent.

[0035] The preparation method of the chitosan-cysteine ​​derivative is as follows: 2.2 parts of chitosan are dispersed in 80 parts of a 1.2wt.% hydrochloric acid aqueous solution, and the mixture is stirred and swelled for 39 minutes to form a homogeneous solution; 1.3 parts of L-cysteine ​​are dissolved in 65 parts of deionized water, 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added, and the activation time is controlled to be 19 minutes; the activated cysteine ​​solution is slowly added dropwise to the chitosan solution, the pH of the system is adjusted to 4.5 with a 1vol.% hydrochloric acid solution, and the reaction is continuously stirred at 30°C for 5 hours. After the reaction is completed, the solution is freeze-dried for 31 hours to obtain the chitosan-cysteine ​​derivative.

[0036] The preparation method of the chitosan-glutathione derivative is as follows: 0.3 parts by weight are dispersed in 2.2 parts of a 1.1 mol / L hydrochloric acid aqueous solution, 10 parts of deionized water are added to form a colloidal dispersion system with a polymer concentration of 1.0 wt.%, the pH of the system is adjusted to 5.8 with 1 vol.% hydrochloric acid, and then 1.9 parts of a 230 mg / mL glutathione aqueous solution are added; 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.08 parts of N-hydroxysuccinimide are added in sequence, the pH value is maintained at 5.9, and the reaction is carried out under magnetic stirring at 19°C for 16 hours; the reaction solution is freeze-dried at -76°C and 0.02 MPa for 47 hours to obtain the chitosan-glutathione derivative.

[0037] The volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:2.8; the solution conductivity of the copper deposition agent is controlled at 8 mS / cm; and the copper deposition rate of the copper deposition agent is 1.9 μm / min.

[0038] The preparation method of an environmentally friendly copper plating agent of this embodiment includes the following steps: S1. Dissolve the quaternized chitosan complexing agent, chitosan-cysteine ​​derivative, and chitosan-glutathione derivative in an ethanol-water mixed solvent according to the ratio. The dissolution process was carried out at a stirring rate of 460 rpm for 39 min and the system temperature was controlled at 28°C. S2. Preparation of prepolymer solution: tea polyphenols, dopamine, potassium citrate trihydrate, ascorbic acid, and glucose were added to the dissolved system in sequence. The mixture was stirred at 360 rpm and maintained at 28°C until completely dissolved. The total addition time was controlled within 13 min. S3. Prepare the coating: Slowly add sodium alginate and sodium citrate, adjust the pH of the system to 5.1, and continue stirring at 460 rpm for 39 minutes to ensure the system is uniform and stable. After the final solution is filtered through a 0.45 μm filter membrane, stand at 5°C in the dark for 16 hours to complete the aging process.

[0039] Example 3 An environmentally friendly copper plating agent comprises the following raw materials in parts by weight: 12 parts of a quaternized chitosan complexing agent, 8 parts of a chitosan-cysteine ​​derivative, 4.6 parts of a chitosan-glutathione derivative, 4.4 parts of tea polyphenols, 4.6 parts of dopamine, 16 parts of potassium citric acid trihydrate, 4 parts of ascorbic acid, 4 parts of glucose, 1.4 parts of sodium alginate, 1.4 parts of sodium citrate, and 68 parts of an ethanol-water mixed solvent.

[0040] The quaternized chitosan complexing agent was prepared by swelling chitosan with a deacetylation degree of 89% and a molecular weight of 220 kDa in an acetic acid-ethanol mixed solvent, reacting it with 2,3-epoxypropyltrimethylammonium chloride under heating and reflux conditions, followed by precipitation, washing, and vacuum drying. The chitosan-cysteine ​​derivative was prepared by swelling chitosan with a deacetylation degree of 89% and a molecular weight of 140 kDa in an acidic aqueous solution, reacting it with preactivated L-cysteine ​​under stirring conditions, and freeze-drying. The polysaccharide-glutathione derivative was prepared by swelling chitosan with a deacetylation degree of 89% and a molecular weight of 140 kDa in an acidic aqueous solution, reacting it with glutathione and a cross-linking agent under stirring conditions at an appropriate pH, and then freeze-drying.

[0041] The preparation method of the quaternized chitosan complexing agent is as follows: in parts by weight, 48 parts of a 1 wt.% acetic acid aqueous solution and 48 parts of ethanol are mixed to form a solvent system, 1.8 parts of chitosan are added, and the mixture is stirred and swelled for 156 minutes, followed by adding 4.1 parts of 2,3-epoxypropyltrimethylammonium chloride, and refluxed at 81° C. for 12 hours. After the reaction is completed, the system is cooled to 28° C., 680 parts of acetone are added to precipitate the product, and the precipitate is collected and then centrifuged and washed four times with a mixed solvent of anhydrous ether and acetone, wherein the volume ratio of anhydrous ether to acetone is 1:12, and finally vacuum dried at -0.09 MPa and 52° C. for 19 hours to obtain the quaternized chitosan complexing agent.

[0042] The preparation method of the chitosan-cysteine ​​derivative is as follows: 3.4 parts of chitosan are dispersed in 110 parts of a 1.3wt.% hydrochloric acid aqueous solution, and the mixture is stirred and swelled for 48 minutes to form a homogeneous solution; 2.0 parts of L-cysteine ​​are dissolved in 80 parts of deionized water, and 0.3 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added, and the activation time is controlled to be 24 minutes; the activated cysteine ​​solution is slowly added dropwise to the chitosan solution, and the pH of the system is adjusted to 4.9 with a 1vol.% hydrochloric acid solution. The mixture is stirred and reacted at 34°C for 6 hours. After the reaction is completed, the solution is freeze-dried for 38 hours to obtain the chitosan-cysteine ​​derivative.

[0043] The preparation method of the chitosan-glutathione derivative is as follows: 0.4 parts by weight are dispersed in 2.5 parts of a 1.1 mol / L hydrochloric acid aqueous solution, 12 parts of deionized water are added to form a colloidal dispersion system with a polymer concentration of 1.2 wt.%, the pH of the system is adjusted to 6.1 with 1 vol.% hydrochloric acid, and then 2.4 parts of a 260 mg / mL glutathione aqueous solution are added; 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.11 parts of N-hydroxysuccinimide are added in sequence, the pH value is maintained at 6.0, and the reaction is carried out under magnetic stirring at 24°C for 19 hours; the reaction solution is freeze-dried at -82°C and 0.03 MPa for 58 hours to obtain the chitosan-glutathione derivative.

[0044] The volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:3.5; the solution conductivity of the copper deposition agent is controlled at 11 mS / cm; and the copper deposition rate of the copper deposition agent is 2.4 μm / min.

[0045] The preparation method of an environmentally friendly copper plating agent of this embodiment includes the following steps: S1. Dissolve the quaternized chitosan complexing agent, chitosan-cysteine ​​derivative, and chitosan-glutathione derivative in an ethanol-water mixed solvent according to the ratio. The dissolution process is carried out at a stirring rate of 520 rpm for 48 min and the system temperature is controlled at 31°C. S2. Preparation of prepolymer solution: tea polyphenols, dopamine, potassium citrate trihydrate, ascorbic acid, and glucose were added to the dissolved system in sequence. The temperature was maintained at 31°C and the stirring speed was 420 rpm. The total addition time was controlled within 16 minutes. S3. Prepare the coating: Slowly add sodium alginate and sodium citrate, adjust the pH of the system to 5.7, and continue stirring at 520 rpm for 48 minutes to ensure the system is uniform and stable. After the final solution is filtered through a 0.45 μm filter membrane, stand at 6°C in the dark for 19 hours to complete the aging process.

[0046] Example 4 An environmentally friendly copper plating agent comprises the following raw materials in parts by weight: 15 parts of a quaternized chitosan complexing agent, 10 parts of a chitosan-cysteine ​​derivative, 6.0 parts of a chitosan-glutathione derivative, 6.0 parts of tea polyphenols, 6.0 parts of dopamine, 20 parts of potassium citric acid trihydrate, 6 parts of ascorbic acid, 5 parts of glucose, 2 parts of sodium alginate, 2.0 parts of sodium citrate, and 80 parts of an ethanol-water mixed solvent.

[0047] The quaternized chitosan complexing agent was prepared by swelling chitosan with a deacetylation degree of 95% and a molecular weight of 300 kDa in an acetic acid-ethanol mixed solvent, reacting it with 2,3-epoxypropyltrimethylammonium chloride under heating reflux conditions, followed by precipitation, washing, and vacuum drying. The chitosan-cysteine ​​derivative was prepared by swelling chitosan with a deacetylation degree of 95% and a molecular weight of 200 kDa in an acidic aqueous solution, reacting it with preactivated L-cysteine ​​under stirring conditions, and freeze-drying. The polysaccharide-glutathione derivative was prepared by swelling chitosan with a deacetylation degree of 95% and a molecular weight of 200 kDa in an acidic aqueous solution, reacting it with glutathione and a cross-linking agent under stirring conditions at an appropriate pH, and then freeze-drying.

[0048] The preparation method of the quaternized chitosan complexing agent comprises the following steps: in parts by weight, 60 parts of a 1 wt.% acetic acid aqueous solution and 60 parts of ethanol are mixed to form a solvent system, 2.0 parts of chitosan are added, stirred and swelled for 180 minutes, and then 4.5 parts of 2,3-epoxypropyltrimethylammonium chloride are added. The reaction is refluxed at 85° C. for 14 hours. After the reaction is completed, the system is cooled to 30° C., 800 parts of acetone are added to precipitate the product, the precipitate is collected and then centrifuged and washed 5 times with a mixed solvent of anhydrous ether and acetone, wherein the volume ratio of anhydrous ether to acetone is 1:13, and finally vacuum dried at -0.10 MPa and 60° C. for 24 hours to obtain the quaternized chitosan complexing agent.

[0049] The preparation method of the chitosan-cysteine ​​derivative is as follows: 5.0 parts of chitosan are dispersed in 150 parts of a 1.5wt.% hydrochloric acid aqueous solution, and the mixture is stirred and swelled for 60 minutes to form a homogeneous solution; 3.0 parts of L-cysteine ​​are dissolved in 100 parts of deionized water, 0.5 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added, and the activation time is controlled to be 30 minutes; the activated cysteine ​​solution is slowly added dropwise to the chitosan solution, the pH of the system is adjusted to 5.5 with a 1vol.% hydrochloric acid solution, and the reaction is continuously stirred at 40°C for 8 hours. After the reaction is completed, the solution is freeze-dried for 48 hours to obtain the chitosan-cysteine ​​derivative.

[0050] The preparation method of the chitosan-glutathione derivative is as follows: 0.5 parts by weight are dispersed in 3.0 parts of a 1.2 mol / L hydrochloric acid aqueous solution, 15 parts of deionized water are added to form a colloidal dispersion system with a polymer concentration of 1.5 wt.%, the pH of the system is adjusted to 6.5 with 1 vol.% hydrochloric acid, and then 3.0 parts of a 300 mg / mL glutathione aqueous solution are added; 0.3 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.15 parts of N-hydroxysuccinimide are added in sequence, the pH value is maintained at 6.2, and the reaction is carried out under magnetic stirring at 30°C for 24 hours; the reaction solution is freeze-dried at -90°C and 0.05 MPa for 72 hours to obtain the chitosan-glutathione derivative.

[0051] The volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:4.5; the solution conductivity of the copper deposition agent is controlled at 15 mS / cm; and the copper deposition rate of the copper deposition agent is 3.0 μm / min.

[0052] The preparation method of an environmentally friendly copper plating agent of this embodiment includes the following steps: S1. Dissolve the quaternized chitosan complexing agent, chitosan-cysteine ​​derivative, and chitosan-glutathione derivative in an ethanol-water mixed solvent according to the ratio. The dissolution process is carried out at a stirring rate of 600 rpm for 60 min and the system temperature is controlled at 35°C. S2. Preparation of prepolymer solution: tea polyphenols, dopamine, potassium citrate trihydrate, ascorbic acid, and glucose were added to the dissolved system in sequence, maintained at 35°C, and stirred at 500 rpm until completely dissolved. The total addition time was controlled within 20 min. S3. Prepare the coating: Slowly add sodium alginate and sodium citrate, adjust the pH of the system to 6.5, and continue stirring at 600 rpm for 60 min to ensure the system is uniform and stable. After the final solution is filtered through a 0.45 μm filter membrane, stand it at 8°C in the dark for 24 h to complete the aging process.

[0053] Comparative Example 1 The method is basically the same as Example 1, except that no quaternized chitosan complexing agent is added, and only ordinary chitosan is used instead.

[0054] Comparative Example 2 The method is basically the same as Example 1, except that no chitosan-cysteine ​​derivative is added and only ordinary chitosan is used instead.

[0055] Comparative Example 3 The method is basically the same as Example 1, except that no chitosan-glutathione derivative is added, and only ordinary chitosan is used instead.

[0056] Comparative Example 4 The method is basically the same as Example 1, except that the amount of the quaternized chitosan complexing agent is increased to 20 parts, which exceeds the scope of the claims.

[0057] Comparative Example 5 The method is basically the same as Example 1, except that when preparing the quaternized chitosan complexing agent, the reflux reaction temperature is increased to 90° C., which exceeds the scope of the claims.

[0058] Comparative Example 6 The method is basically the same as Example 1, except that tea polyphenols and dopamine are not added.

[0059] Comparative Example 7 The method is basically the same as Example 1, except that the volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:5.0, which is beyond the scope of the claims.

[0060] Comparative Example 8 The method is basically the same as Example 1, except that 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride is not added as an activator during the preparation of the chitosan-cysteine ​​derivative.

[0061] Performance testing: Copper layer adhesion test: Based on the ASTM D3359-17 standard method, electroless copper deposition was performed on a 100mm x 100mm FR-4 substrate, with a deposit thickness of 2μm. A cross-hatch method was used for peel testing using 3M tape. The cross-hatch area was observed with a magnifying glass, and the adhesion between the copper layer and the substrate was rated on a scale of 0-5.

[0062] Copper layer uniformity and porosity testing: Referring to IPC-TM-650 2.2.12, the surface morphology of the deposited copper layer was observed using a scanning electron microscope (SEM), and the composition distribution of the copper layer was analyzed using EDS spectroscopy. Electrochemical impedance spectroscopy (EIS) testing was also used to evaluate the density of the copper layer.

[0063] Environmental friendliness assessment: Based on the ISO 14040 life cycle assessment method, environmental indicators such as COD, BOD, and heavy metal ion content were measured during the copper deposition process. Heavy metal content in wastewater was measured using atomic absorption spectroscopy (AAS), and chemical oxygen demand (COD) was determined using the potassium dichromate method.

[0064] Corrosion resistance of the coating: According to ASTM B117-19, the plated samples were placed in a 5wt.% sodium chloride salt spray chamber at 35±2°C for 168 hours of accelerated corrosion testing. Polarization curves and corrosion potentials were measured using an electrochemical workstation.

[0065] The properties of the environmentally friendly copper plating agents of Examples 1 to 4 and Comparative Examples 1 to 8 are summarized in Table 1.

[0066] Table 1 Performance summary of environmentally friendly copper plating agents of Examples 1 to 4 and Comparative Examples 1 to 8

[0067] Quaternized chitosan complexing agent is a key component for improving the bonding strength and corrosion resistance of the copper layer. Its absence will lead to a significant decrease in these two properties; cysteine ​​derivatives mainly affect the bonding strength between the copper layer and the substrate, and have a slight effect on other properties; glutathione derivatives have relatively little effect on the performance of copper deposition; the amount of complexing agent used beyond the optimal range will lead to an increase in the COD of the wastewater; too high a reaction temperature will affect the molecular structure and cross-linking degree of the product, and reduce the density of the copper layer; tea polyphenols and dopamine are important components for improving corrosion resistance, but their reduction will reduce the COD value; the ratio of ethanol-water mixed solvent has no obvious effect on the performance of copper deposition; the use of activator plays a key role in improving the bonding strength and density of the copper layer, and the lack of activator will significantly reduce these two performance indicators.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that any equivalent structural transformations made within the scope of the present invention using the contents of the present invention's description and drawings should be included within the scope of protection of the claims of the present invention.

Claims

1. An environmentally friendly copper deposition agent, characterized in that: The invention comprises the following raw materials in parts by weight: 8-15 parts of quaternary ammonium chitosan complexing agent, 5-10 parts of chitosan-cysteine ​​derivative, 2.5-6.0 parts of chitosan-glutathione derivative, 2.0-6.0 parts of tea polyphenols, 2.5-6.0 parts of dopamine, 10-20 parts of potassium citrate trihydrate, 2-6 parts of ascorbic acid, 2-5 parts of glucose, 0.5-2 parts of sodium alginate, 0.5-2.0 parts of sodium citrate and 50-80 parts of ethanol-water mixed solvent.

2. An environmentally friendly copper deposition agent as claimed in claim 1, characterized in that: The quaternized chitosan complexing agent is prepared by swelling chitosan with a deacetylation degree of 80-95% and a molecular weight of 100-300 kDa in an acetic acid-ethanol mixed solvent, reacting with 2,3-epoxypropyltrimethylammonium chloride under heating reflux conditions, and then precipitating, washing and vacuum drying. The chitosan-cysteine ​​derivative is prepared by swelling chitosan with a deacetylation degree of 80-95% and a molecular weight of 50-200 kDa in an acidic aqueous solution, reacting with preactivated L-cysteine ​​under stirring conditions, and freeze-drying; The chitosan-glutathione derivative is prepared by swelling chitosan with a deacetylation degree of 80-95% and a molecular weight of 50-200 kDa in an acidic aqueous solution, stirring and reacting with glutathione and a cross-linking agent under suitable pH conditions, and freeze-drying.

3. An environmentally friendly copper deposition agent as claimed in claim 1 or 2, characterized in that: The preparation method of the quaternary ammonium chitosan complexing agent comprises the following steps: by weight, 30-60 parts of 1wt.% acetic acid aqueous solution and 30-60 parts of ethanol are mixed to form a solvent system, 1.5-2.0 parts of chitosan are added, stirred and swollen for 120-180 minutes, then 3.5-4.5 parts of 2,3-epoxypropyltrimethylammonium chloride are added, reflux reaction is carried out at 75-85°C for 10-14 hours, after the reaction is completed, the system is cooled to 25-30°C, 500-800 parts of acetone are added to precipitate the product, the precipitate is collected and then centrifuged and washed 3-5 times with a mixed solvent of anhydrous ether and acetone, wherein the volume ratio of anhydrous ether to acetone is 1:(10-13), and finally vacuum dried at -0.08-0.10MPa and 40-60°C for 12-24 hours to obtain the quaternary ammonium chitosan complexing agent.

4. An environmentally friendly copper deposition agent as claimed in claim 1 or 2, characterized in that: The preparation method of the chitosan-cysteine ​​derivative is as follows: by weight, 1.0-5.0 parts of chitosan are dispersed in 50-150 parts of 1.0-1.5wt.% hydrochloric acid aqueous solution, and stirred and swollen for 30-60 minutes to form a homogeneous solution; 0.5-3.0 parts of L-cysteine ​​are dissolved in 50-100 parts of deionized water, 0.1-0.5 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride are added, and the activation time is controlled to be 15-30 minutes; the activated cysteine ​​solution is slowly dripped into the chitosan solution, the pH of the system is adjusted to 4.0-5.5 with 1vol.% hydrochloric acid solution, and the reaction is continuously stirred at 25-40°C for 4-8 hours. After the reaction is completed, the solution is freeze-dried for 24-48 hours to obtain the chitosan-cysteine ​​derivative.

5. An environmentally friendly copper deposition agent as claimed in claim 1 or 2, characterized in that: The preparation method of the chitosan-glutathione derivative is as follows: by weight, 0.2-0.5 parts of chitosan-glutathione derivative are dispersed in 1.8-3.0 parts of 1.0-1.2 mol / L hydrochloric acid aqueous solution, 8-15 parts of deionized water are added to form a colloidal dispersion system with a polymer concentration of 0.8%-1.5wt.%, and 1.5-3.0 parts of glutathione with a concentration of 200-300 mg / mL are added after adjusting the pH of the system to 5.5-6.5 with 1vol.% hydrochloric acid. Glytidine aqueous solution; add 0.1-0.3 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and 0.05-0.15 parts of N-hydroxysuccinimide in sequence, maintain the pH value at 5.8-6.2, and react with magnetic stirring at 15-30°C for 12-24h; freeze-dry the solution after the reaction at -70--90°C and 0.01-0.05MPa for 36-72h to obtain chitosan-glutathione derivatives.

6. An environmentally friendly copper deposition agent as claimed in claim 1, characterized in that: The volume ratio of ethanol to water in the ethanol-water mixed solvent is 1:(2.0-4.5).

7. An environmentally friendly copper deposition agent as claimed in claim 1, characterized in that: The solution conductivity of the copper plating agent is controlled at 5-15 mS / cm.

8. An environmentally friendly copper deposition agent as claimed in claim 1, characterized in that: The copper deposition rate of the copper deposition agent is 1.5-3.0 μm / min.

9. A method for preparing an environmentally friendly copper deposition agent as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S1. According to the ratio, the quaternary ammonium chitosan complexing agent, chitosan-cysteine ​​derivative and chitosan-glutathione derivative are dissolved in an ethanol-water mixed solvent, and the dissolution process is carried out at a stirring rate of 400-600 rpm for 30-60 min, and the system temperature is controlled at 25-35°C; S2. Preparation of prepolymer solution: tea polyphenols, dopamine, potassium citrate trihydrate, ascorbic acid and glucose were added to the dissolved system in sequence, the temperature was maintained at 25 to 35°C, and the stirring speed was 300 to 500 rpm until completely dissolved. The total addition time was controlled within 10 to 20 min; S3. Prepare the coating: slowly add sodium alginate and sodium citrate, adjust the pH of the system to 4.5-6.5, continue stirring at 400-600 rpm for 30-60 min to ensure that the system is uniform and stable. After the final solution is filtered through a 0.45 μm filter membrane, stand at 4-8°C in the dark for 12-24 h to complete the aging process.

10. Use of the environmentally friendly copper deposition agent as claimed in any one of claims 1 to 8 or the environmentally friendly copper deposition agent prepared by the preparation method as claimed in claim 9 in the manufacture of electronic circuits, printed circuit copper deposition, electromagnetic shielding coatings and flexible electronic devices.

Citation Information

Patent Citations

  • Chemical copper plating solution of sodium hypophosphite disodium edetate system

    CN101698936B

  • Quaternized chitosan microsphere loaded copper metal organic framework material as well as preparation method and application thereof

    CN117859767A

  • Copper electroplating solution for chip packaging and preparation method thereof

    CN118292061A

  • High-activity chemical copper plating solution and chemical copper plating method

    CN119307899A

  • Thiolated polysaccharide derivative hydrogel, preparation method therefor, and application thereof

    WO2022222907A1